Remote ischaemic conditioning before hospital admission, as a complement to angioplasty, and effect on myocardial salvage in patients with acute myocardial infarction: a randomised trial. - Bøtker, H; Kharbanda, R; Schmidt, MR; Bøttcher, M; Kaltoft, A; Terkelsen, C; Munk, K; Andersen, N; Hansen, T; Trautner, S; Lassen, J; Christiansen, E; et al. (2010)
BACKGROUND: Remote ischaemic preconditioning attenuates cardiac injury at elective surgery and angioplasty. We tested the hypothesis that remote ischaemic conditioning during evolving ST-elevation myocardial infarction, and done before primary percutaneous coronary intervention, increases myocardial salvage. METHODS: 333 consecutive adult patients with a suspected first acute myocardial infarction were randomly assigned in a 1:1 ratio by computerised block randomisation to receive primary percutaneous coronary intervention with (n=166 patients) versus without (n=167) remote conditioning (intermittent arm ischaemia through four cycles of 5-min inflation and 5-min deflation of a blood-pressure cuff). Allocation was concealed with opaque sealed envelopes. Patients received remote conditioning during transport to hospital, and primary percutaneous coronary intervention in hospital. The primary endpoint was myocardial salvage index at 30 days after primary percutaneous coronary intervention, measured by myocardial perfusion imaging as the proportion of the area at risk salvaged by treatment; analysis was per protocol. This study is registered with ClinicalTrials.gov, number NCT00435266. FINDINGS: 82 patients were excluded on arrival at hospital because they did not meet inclusion criteria, 32 were lost to follow-up, and 77 did not complete the follow-up with data for salvage index. Median salvage index was 0.75 (IQR 0.50-0.93, n=73) in the remote conditioning group versus 0.55 (0.35-0.88, n=69) in the control group, with median difference of 0.10 (95% CI 0.01-0.22; p=0.0333); mean salvage index was 0.69 (SD 0.27) versus 0.57 (0.26), with mean difference of 0.12 (95% CI 0.01-0.21; p=0.0333). Major adverse coronary events were death (n=3 per group), reinfarction (n=1 per group), and heart failure (n=3 per group). INTERPRETATION: Remote ischaemic conditioning before hospital admission increases myocardial salvage, and has a favourable safety profile. Our findings merit a larger trial to establish the effect of remote conditioning on clinical outcomes. FUNDING: Fondation Leducq.